Aerodynamic optimization for variable-speed wind turbines based on wind energy capture efficiency - Yin, Minghui (2020)
The variable-speed wind turbine (VSWT) is a dominant type of wind power generator. In order to improve wind energy production, its off-design performance has been considered for aerodynamic optimization, since it frequently operates at non-optimal tip speed ratio (TSR) in the maximum power point tracking (MPPT) mode. In this paper, the objective function for multi-point aerodynamic optimization is firstly derived as wind energy capture efficiency. Then, a new multi-point aerodynamic design method whose objective function can approximate wind energy capture efficiency is proposed. Since the proposed optimization aims to increase the closed-loop efficiency with a clear physical meaning, static aerodynamic performance and MPPT dynamics can be better coordinated and correspondingly higher wind energy production of VSWTs can be achieved. Finally, using the 1.5 MW and 5.0 MW VSWTs developed by National Renewable Energy Laboratory (NREL) as the baseline, the proposed method is verified by simulations with commercial software Bladed and experiment test on a wind turbine testbed.